KETELADANAN GURU PAI PADA ASPEK KEPRIBADIAN UNTUK MENGEMBANGKAN KARAKTER RELIGIUS SISWA DI SDIT SUIS BOGOR (Al Irfan : Jurnal Ilmu Pendidikan dan Penelitian, 2025)
The personality competence of Islamic Religious Education (PAI) teachers has an important role in developing the religious character of students through example. However, the condition of some PAI teachers has not been consistent in implementing the personality competencies of teachers. This study aims to examine in depth how the contribution of the personality competencies of PAI teachers, especially in the aspects of work ethic, authority, and wisdom, to the development of students' religious character at SDIT SUIS Bogor. This study uses a qualitative research method with a phenomenological approach. The data collection methods used are observation, interviews and documentation. The validity of the data in this study was carried out the source triangulation technique and the method triangulation technique. The results of the study show that the personality competence of PAI teachers has an important role in developing the religious character of students. The aspects of work ethic, authority, and the wisdom of teachers have proven to contribute positively.